THEORETICAL FOUNDATIONS OF THE CUSTOMER EXPERIENCE MANAGEMENT MECHANISM - Скороходов, Іван М.; Євсейцева, Олена С.; Шіковець, Катерина О. (Journal of Strategic Economic Research, 2025)
The article is devoted to the internal structure and external influences of the customer experience management mechanism. It is established that the customer experience management mechanism is a system comprising methods, means, tools, principles, and rules through which an impact is exerted on the object of management (the formed customer experience) to achieve specified goals. The mechanism includes various elements – purpose, management tasks, stages, functions, principles, methods, and tools – that interact to ensure the effective functioning and development of the object of management. The foundation of the mechanism is the customer experience management system in terms of its components and the driving forces that set this system in motion: its implementation stages, as well as the goals and tasks of such management. It is substantiated that the determinants of the mechanism’s effectiveness lie in ensuring its functioning and encompass a set of external factors of diverse nature: financial, methodological, technical, technological, material, and human-resource support. Implementation of the mechanism relies on contemporary instruments – CRM systems, customer experience assessment methods, social networks, and online platforms – which enable systematic monitoring and timely responses to changes in consumer needs. A special role is played by the principle of continuous improvement, which allows for the flexible adaptation of business processes and marketing strategies to conditions of intense competition and rapid technological change. An important factor in the mechanism’s performance is external support, which includes financial, methodological, technical, technological, material, and human resources. The aggregate of these elements creates a basis for the timely identification of challenges and risks, the minimization of threats to the economic security of business entities, and the achievement of strategic objectives. Effective customer experience management contributes to higher levels of customer satisfaction and loyalty, the formation of a positive brand image, growth in sales and profitability, and provides the enterprise with a sustainable long-term competitive advantage in the market. Thus, the implementation of a customer experience management system is not only an instrument of marketing policy but also a strategic factor in the successful development of the enterprise in the digital economy.